Get Your Business Funded : Creative Methods for Getting the Money you Need - Strauss, Steven D., 1958- (Hoboken John Wiley, 2011)
"Explore the many options available to get the money you need for your business Whether your business is a new start-up, an established company attempting to grow, or somewhere in between, Get Your Business Funded gives you the full range of options for raising capital in today's challenging economy. Covering everything from bank loans to angel investors to equity financing to more unorthodox methods, this complete guide uses clear, easy-to-understand language to explain each approach. Divided into two sections: "Sources and Funding" and "What You Need to Know" Explains such unorthodox financing sources as peer-to-peer lending, online grants, business plan competitions, and the "friends and family plan" Reveals untapped funding streams available through the government Follows on the success of the author's previous work The Small Business Bible Pick up this reader-friendly guide and discover the many ways you can Get Your Business Funded right now"
Include Index
Keywords: New business enterprises--Finance -- Small business--Finance -- Venture capital